(untitled) (Research, Society and Development, 2024)
The present work deals with the diagnosis of the use of reinforced concrete within civil construction, with the aim of recognizing the importance and need for reinforced concrete in civil works and, based on the insight gained, presenting a bibliographical review of the case. And after that, the mechanisms that lead to the origins of approvals and met requirements are presented. Below are some diagnoses and precautions regarding the incident. Finally, a study is carried out on a reinforced concrete structure and the need for reinforcement, maintenance and durability of structures made of reinforced concrete are presented and analyzed. For this, the case study methodology was used, where some cases of pathology in reinforced concrete were observed in some buildings in the municipality of Açailândia-MA, and thus the main objective will be to diagnose these pathologies in the structures of the municipality and identify the possible cause. of why this pathology occurred in the structure.